Ewolucja polskiego systemu wykroczeń — przez autorytaryzm do demokracji. Część 2 - Łucarz, Katarzyna; Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The authors of this study present the transformations of the Polish system of petty oﬀ ences law by discussing the normative shape and searching for optimal legislative solutions. The reﬂ ections are based on historical references, by studying changes in this area of law, marked by many legal and practical issues. The historical approach facilitates on analysis of tendency which occurred in the process of developing the law of petty oﬀ ences, systemic inﬂuences on the organizational structures created within it, and the material and procedural shape. Historical threads include the basic conditions for the development of liability for petty oﬀences, taking into account the assumptions of the inter-war period, through the times of authoritarianism to the present day. During the last century, the system of petty oﬀences was considered as an area which searches for legal solutions to counteract administrative lawlessness or criminal lawlessness with less social noxiousness of the act that is subject to political requirements in various degree and controlled by the government. The wide scope of the presented issue entails necessity to separate two parts. First — including the period up to the 1970s, that is until the establishment of the Code of Petty Oﬀenses 1971, and the second — to modern times, in which this Code is still in force.
Keywords: wykroczenie; delikt administracyjny; prawo karno-administracyjne; kolegia orzekające